Addressing Future Epidemics: Historical Human Rights Lessons from the AIDS Pandemic - Ambar Mehta; Thomas C. Quinn (Case Western Reserve University, 2016)
Introduction: The Ebola epidemic in West Africa sparked many ethical and polarizing public health questions on how to adequately control transmission of the virus. These deliberations had and will continue to influence patients, healthcare workers, public perceptions of disease, and governmental responses. Such extensive and potential ramifications warranted an analysis of prior epidemics to sufficiently inform policy makers and prepare them and other authorities for future epidemics. We analyzed how the general public, medical institutions, federal government, and patients themselves responded during the early stages of the AIDS pandemic in two different countries and cultures, the United States and India. Discussion: Our analysis identified four key findings pertaining to the human rights of patients and healthcare workers and to the crucial roles of the government and medical community. The first demands that authoritative officials acknowledge the presence of high-risk behaviors and properly educate the public without stigmatizing groups of individuals. For this task, the medical community and federal government must form and display to the public a respectful and collaborative partnership towards battling the epidemic. These two synergistic endeavors will then allow appropriate officials to implement effective, yet civil, interventions for limiting transmission. Finally, the same officials must ensure that their interventions maintain the human rights of high-risk populations and of healthcare workers. Conclusions: Applying these findings to future epidemics of infectious diseases can aid policy makers in navigating complicated ethical and public health questions, and help prevent them from repeating past mistakes in handling epidemics.